PELATIHAN PUBLIC SPEAKING UNTUK MENINGKATKAN KEMAMPUAN PRESENTASI - Herwina, Wiwin; Waliyyan, Azka; Herdiani, Sherli; Fathonah, Eka Amalia Siti; Farabila, Syalsha; Nofianti, Febi; Rahmawati, Dewi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Public speaking skills are an important part of every activity, especially activities in the academic field. In reality, there are still very few school students who have public speaking skills. Based on this, we, Siliwangi University PLP (introduction to the professional field) participants who were assigned to the Tasikmalaya Regency work Training Center, took the initiative to provide Public Speaking Training services to PKL (field practice) students. This training was carried out by analyzing the participants' needs first, so that later after PKL they could present the results of their reports. to the hearing board properly. The methods used in this training are providing material, discussion and demonstration. In the training activities carried out, exploring students' potential was done by asking them to speak in public without preparation. Then it ended with them doing public speaking again by making a speech. This is demonstrated by their ability to apply knowledge while taking public speaking training. After the training was carried out, it was seen that there was good potential for the Job Training Center PKL students in public speaking. Potential will simply evaporate if it is not continuously sharpened to face the world of college and future employment